1979
DOI: 10.1044/jshr.2201.37
|View full text |Cite
|
Sign up to set email alerts
|

Speech Clinicians' Attribution of Personality Traits as a Function of Stuttering Severity

Abstract: Thirty-six speech-language pathologists participated in a study to evaluate clinicians' preconceptions of persons who stutter. Each rated a designated construct (the normally fluent individual, the mild stutterer, the moderate stutterer, the severe stutterer) using a personality trait scale. Results indicated that clinicians stereotypically assign negative personality traits to all levels of stuttering severity relative to normal. Their ratings further demonstrated that stutterers are generally considered to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 0 publications
7
41
0
2
Order By: Relevance
“…These findings corroborate those obtained for other speech disorders, including stuttering [Yairi and Williams, 1970;Wil liams, 1971, 1976;Turnbaugh et al. 1979], lisping [Silverman, 1976;Mowrer et al.…”
Section: Discussionsupporting
confidence: 81%
“…These findings corroborate those obtained for other speech disorders, including stuttering [Yairi and Williams, 1970;Wil liams, 1971, 1976;Turnbaugh et al. 1979], lisping [Silverman, 1976;Mowrer et al.…”
Section: Discussionsupporting
confidence: 81%
“…Studies support the notion that children and adolescents who stutter are stereotyped as more anxious, stressed or nervous than their more fluent counterparts (Crowe & Walton, 1981;Ham, 1990;Ruscello et al, 1994;Turnbaugh et al, 1979;Woods & Williams, 1971). The current findings make an important contribution about anxiety and stuttering in adolescents, especially given the limited number of studies published.…”
Section: Discussionsupporting
confidence: 51%
“…Stuttering is an unpredictable disorder (Bloodstein, 1995;Guitar, 2005;Manning, 2001;Shapiro, 1999) with conflicting and variable responses from fluent communication partners and reported negative communication experiences (Bebout & Bradford, 1992;Ham, 1990;Ruscello, Lass, Schmitt, & Pannbacker, 1994;Turnbaugh, Guitar, & Hoffman, 1979;Woods & Williams, 1971). Data from qualitative studies suggest suffering, helplessness, shame, and stigma may be core experiences for some adults who stutter (Corcoran & Stewart, 1998;Crichton-Smith, 2002;Klompas & Ross, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…shown to exist among parents (Crowe & Cooper, 1977;Fowlie & Cooper, 1978;Woods & Williams, 1976), speech language clinicians Cooper & Rustin, 1985;Lass, Ruscello, Pannbacker, Schmitt, & Everly-Myers, 1989;Turnbaugh, Guitar, & Hoffman, 1979), students (St. Louis & Lass, 1981;White & Collins, 1984), store clerks (McDonald & Frick, 1954), teachers (Crowe & Cooper, 1977;Crowe & Walton, 1981;Lass, Ruscello, Schmitt, Pannbacker, Orlando, Dean, Ruziska, & Bradshaw), vocational rehabilitation counselors , and employers .…”
Section: Stereotypes Of Stutterersmentioning
confidence: 99%
“…In an attempt to determine if stuttering severity affected this negative stereotype, Turnbaugh et al (1979), employing a semantic differential personality trait scale had speech-language pathologists rate mild, moderate, and severe hypothetical stuttering individuals. They found that stutterers, regardless of stuttering severity, received negative stereotypes in comparison to nonstutterers.…”
Section: Stereotypes Of Stutterersmentioning
confidence: 99%